Iron dextran and farbegen compared as methods of preventing iron deficiency anemia in neonatal pigs - D A Schoneweis; G L Allee (Kansas Agricultural Experiment Station Research Reports, 1977)
The experiment suggests that a primary need of the neonatal pig is iron and that hematinics such as cobalt and liver extract are of little value if iron is insufficient.; Swine Day, Manhattan, KS, November 10, 1977
Keywords: Swine day; 1977; Kansas Agricultural Experiment Station contribution; no. 78-101-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 312; Swine; Iron dextran; Farbegen; Iron deficiency anemia; Neonatal pigs